2020
DOI: 10.1038/s41436-020-0880-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved structural variant interpretation for hereditary cancer susceptibility using long-read sequencing

Abstract: Purpose Structural variants (SVs) may be an underestimated cause of hereditary cancer syndromes given the current limitations of short-read next-generation sequencing. Here we investigated the utility of long-read sequencing in resolving germline SVs in cancer susceptibility genes detected through short-read genome sequencing. Methods Known or suspected deleterious germline SVs were identified using Illumina genome sequencing across a cohort of 669 advanced cancer patients with paired tumor genome and transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…For example, short reads are generally considered to have a poorer sensitivity for detecting structural variants than long reads [ 133 ]. Recently, long-read sequencing was used to clarify suspected structural variants in the germlines of hereditary cancer patients [ 134 ], and there are known examples of large deletions or rearrangements causing LS, such as the Finnish MLH1 founder variant [ 85 , 92 ] and Australian MHS2 inversion [ 93 ] described earlier. In addition, novel base-callers being developed for long-read sequencing data may be able to detect base modifications from subtle effects on sequencing dynamics [ 132 ], which could facilitate detection of germline epigenetic modifications of MMR genes, such as those estimated to account for 2–3% of MLH1 -associated LS [ 73 , 74 , 75 ].…”
Section: The Next Generation Of Ls Screeningmentioning
confidence: 99%
“…For example, short reads are generally considered to have a poorer sensitivity for detecting structural variants than long reads [ 133 ]. Recently, long-read sequencing was used to clarify suspected structural variants in the germlines of hereditary cancer patients [ 134 ], and there are known examples of large deletions or rearrangements causing LS, such as the Finnish MLH1 founder variant [ 85 , 92 ] and Australian MHS2 inversion [ 93 ] described earlier. In addition, novel base-callers being developed for long-read sequencing data may be able to detect base modifications from subtle effects on sequencing dynamics [ 132 ], which could facilitate detection of germline epigenetic modifications of MMR genes, such as those estimated to account for 2–3% of MLH1 -associated LS [ 73 , 74 , 75 ].…”
Section: The Next Generation Of Ls Screeningmentioning
confidence: 99%
“…The first rearrangement, which does not result in any copy number change of coding exons, introduces a singleexon inversion. Thibodeau et al 8 recently reported this same inversion, and RNA sequencing demonstrated that this results in skipping of exon 5. The second rearrangement constitutes a large deletion with six insertion components, including a 2.7kb sequence in inverted orientation.…”
Section: Categorical Description Of Svsmentioning
confidence: 78%
“…In addition, long-read sequencing simplifies the characterization of breakpoint signatures and is helpful to resolve suspicious or complex signals detected in short-read sequencing. 8 The SVs discovered in germline testing exhibit many features that are also found in somatic SVs. 65 Thus, many SV detection algorithms show equivalent performance for germline sequencing and tumor testing with variant allele fractions as low as 20%.…”
Section: Study Limitationsmentioning
confidence: 99%
“…It is also important to consider the source of the DNA sample (Trost et al, 2019), which can influence the quality and amount of input DNA used for sequencing. Each of these factors may in turn impact all aspects of data generated, in particular when long-read technologies are used rather than the short-read sequencing presented here (Wang et al, 2019;Thibodeau et al, 2020).…”
Section: Discussionmentioning
confidence: 99%